Increase in albumin, IgG, and IgM blood-nerve barrier indices in human diabetic neuropathy. - Poduslo, J F (1988)
The albumin (Alb), IgG, and IgM concentrations in the endoneurium of fascicular sural nerve biopsy samples were evaluated in controls (n = 9 or 10), diabetic patients without neuropathy (n = 6), and diabetic patients with polyneuropathy (n = 17 or 18). These values were significantly increased in diabetic patients with and without neuropathy when expressed both per endoneurial dry weight or endoneurial total protein compared to biopsy samples from healthy controls. When these concentrations, expressed per endoneurial total protein, were related to plasma concentrations similarly expressed, the resulting blood-nerve barrier (BNB) indices were significantly increased for Alb (6.1 times; P less than 0.00001), IgG (4.9 times; P = 0.00037), and IgM (2.7 times; P = 0.015). The diabetic patients without neuropathy (defined as having an index of pathology of greater than 0.65; a measure of the severity of the pathological abnormality based on morphological criteria) also had significant increases in two of these BNB indices that were intermediate between the diabetic neuropathy patients and controls (Alb, 3.9 times controls; P = 0.00002: IgG, 4.6 times controls; P = 0.00016: IgM, 1.8 times controls; not significant). No correlations were observed between the endoneurial concentrations of these plasma proteins or the BNB indices and the index of pathology, suggesting that these increases in endoneurial plasma proteins precede the pathologic alterations. The increased values for the diabetics in the absence of pathological abnormalities may prove useful in predicting neuropathic complications. The ratio of the IgG-BNB index to the Alb-BNB index was decreased 19%, and the ratio of the IgM-BNB index to the Alb-BNB index was decreased 56% in diabetic neuropathy patients compared to controls. Although the IgG and IgM concentrations are increased in the diabetic endoneurium, the Alb increase is greater and a mechanism other than size indiscriminate extravasation of plasma proteins, therefore, is suggested. Morphometric assessment of the endoneurial compartments, which would be expected to contain these plasma proteins, suggests that they are not altered in diabetic neuropathy; hence, it is hypothesized that the observed increase in endoneurial concentration of these plasma proteins results from altered transport through the endothelial or perineurial barrier, which supports an underlying vascular mechanism in the development of diabetic polyneuropathy.